The situation of Mauretania in late II Triumvirate and early Augustan - Amela Valverde, Luis (Gerión. Revista de Historia Antigua, 2013)
The situation in Mauretania after the death of Bocchus II is one of the most interesting themes of the final period of the republic in northern Africa. In this paper we attempt to make an approach to this interesting question.